2001
DOI: 10.1073/pnas.161151798
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage-inducible gene p33ING2 negatively regulates cell proliferation through acetylation of p53

Abstract: The p33ING1 protein is a regulator of cell cycle, senescence, and apoptosis. Three alternatively spliced transcripts of p33ING1 encode p47ING1a, p33ING1b, and p24ING1c. We cloned an additional ING family member, p33ING2͞ING1L. Unlike p33ING1b, p33ING2 is induced by the DNA-damaging agents etoposide and neocarzinostatin. p33ING1b and p33ING2 negatively regulate cell growth and survival in a p53-dependent manner through induction of G 1-phase cell-cycle arrest and apoptosis. p33ING2 strongly enhances the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
236
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(247 citation statements)
references
References 52 publications
9
236
2
Order By: Relevance
“…ING1 downregulation was observed in different tumor types (breast, gastric, esophageal, blood, lung and brain) (Gong et al, 2005), whereas protein mislocalization was described in tumors of different origin (Nouman et al, 2002). ING2 expression was reduced in colorectal, hepatocellular carcinoma, prostate, pancreatic, lung cancer and cutaneous melanoma (Nagashima et al, 2001;Lu et al, 2006;Okano et al, 2006). Allelic loss and reduced expression of ING3 have been also reported (Gunduz et al, 2002;Nagashima et al, 2003).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…ING1 downregulation was observed in different tumor types (breast, gastric, esophageal, blood, lung and brain) (Gong et al, 2005), whereas protein mislocalization was described in tumors of different origin (Nouman et al, 2002). ING2 expression was reduced in colorectal, hepatocellular carcinoma, prostate, pancreatic, lung cancer and cutaneous melanoma (Nagashima et al, 2001;Lu et al, 2006;Okano et al, 2006). Allelic loss and reduced expression of ING3 have been also reported (Gunduz et al, 2002;Nagashima et al, 2003).…”
Section: Introductionmentioning
confidence: 86%
“…A physical association between ING proteins and p53 has been reported in different studies. Furthermore, ING proteins may modulate p53 activity by enhancing p53 acetylation at Lys-382 (Nagashima et al, 2001;Kataoka et al, 2003;Russell et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The founding member of the family, ING1, was initially discovered by a screen designed to identify genes that allow neoplastic transformation when repressed (Garkavtsev et al, 1996). Subsequently, four other members of the family, ING2-ING5, were identified by a homology search (Nagashima et al, 2001Shiseki et al, 2003). INGs are nuclear proteins and one important structural feature of these proteins is the presence of a highly conserved plant homeodomain zinc-finger in their C-terminal part.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between ING2 and this modified histone allows the stabilization of the Sin3A/HDAC complex onto the promoter of the proliferative genes c-myc and cyclin D1 to mediate their repression (Shi et al, 2006). Initially, ING2 was reported to enhance p53 acetylation to negatively regulate cell growth, to induce apoptosis and to regulate the onset of replicative senescence (Nagashima et al, 2001;Pedeux et al, 2005). In these pathways, it has been reported that the lipid signaling molecule phosphatidylinositol-5-phosphate binds and activates ING2 (Gozani et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…ING5) are implicated in a variety of processes including gene transcription, oncogenesis, apoptosis, DNA repair, and cell cycle control (Nagashima et al, 2001Feng et al, 2002;Shiseki et al, 2003;Campos et al, 2004). ING4, a novel member of the ING family, has recently emerged as a strong tumor suppressor gene that functions in cell proliferation, contact inhibition, and angiogenesis (Garkavtsev et al, 2004;Kim et al, 2004).…”
mentioning
confidence: 99%